Pregnancy Induced Hypertension and Lipid Profile of Obese and Normal Weight Pregnant Women. A Comparative Study - Fakharunissa; Hingoro, Rasheeda; Baloch, Sanobar (Pakistan Journal of Medical & Health Sciences, 2022)
Maternal dyslipidemia and hypertension are risk factors and correlated with the pregnancy complications which creates serious biochemical and physiological effects on neonatal outcome. It was concluded that different variables such as systolic and diastolic blood pressure serum cholesterol, triglyceride, low density lipoproteins and High density lipoproteins levels (140±11.13, 90±21.9, 169±12.31, 146±2.10, 170±11.10, 49±12.10) and (200±10.12, 100±21.19, 226±10.13, 200±12.11, 230±14.13, 37±16.19) of Group H and Group N have a significant changes (<0.005) as compared to the control Group N (122±1.3, 80±2.9, 120±23,130±21, 115±10, 42±20).